DIGITAL TRANSFORMATION OF INDUSTRIAL ENTERPRISES OF THE REPUBLIC OF BELARUS: ECONOMIC CONTENT, TYPES AND GOALS - I. A. Zubritskaya (Цифровая трансформация)
The article is devoted to a complex research of the topical issues affecting scope of digital transformation of the industry. The reveals the economic content of digital transformation of the industry as the processes of digital transformation of production management by introducing technical and technological means of global megatrends, characteristic for the fourth industrial revolution, and the author also examines the economic aspects of digital transformation of the industry that affect the economic growth of the country as a whole. Based on the results of previous research, the author systematizes the main goals of digital transformation of industrial enterprises, reveals the prospects for the introduction of technical and technological means of global megatrends, characteristic of the fourth industrial revolution, as well as the influence of the institutional environment on the intensity of digital transformation of industry, transformation of industrial production. The article analyzes the existing models of digital transformation of industry as possible standards for digital transformation of an industrial enterprise and suggests an integration model of end-to-end digital transformation of industry based on matrix and industry models that will allow to build an inter-industry digital network in a digital economy. In accordance with the adopted digital agendas of the Republic of Belarus and the EEC, the proposed model is based on the end-to-end interaction between all participants in the value chains of industrial products, which are equally involved in production and economic planning, management, control of the creation and implementation of industrial high-tech products.